Efektivitas Pemeriksaan Pajak Penghasilan Badan: Studi pada KPP Pratama Padang Sidempuan: (The Effectiveness of Corporate Income Tax Audits: A Study at the Padang Sidempuan Primary Tax Office) - Muhammad Firzah (Transparansi : Jurnal Ilmiah Ilmu Administrasi, 2025)
Tax audit serves as a strategic instrument in the government’s efforts to enhance state revenue. However, its implementation in the field has not yet fully achieved the established targets, as indicated by the substantial number of fiscal adjustments to income and expense components that do not comply with tax regulations. This study aims to analyze the effectiveness of tax audit implementation on the Annual Income Tax Return (SPT) of corporate taxpayers at the Primary Tax Office (KPP Pratama) Padang Sidempuan, under the Regional Office of the Directorate General of Taxes (DJP) North Sumatra II. The research method employed is a descriptive qualitative approach through field observations and interviews. The results reveal that the effectiveness of tax audit implementation remains suboptimal. This condition is attributed to the decline in tax audit revenue realization, delays in the submission of tax returns by taxpayers, and the limited number of tax auditors relative to the size of the working area and audit targets. Nevertheless, the implementation of tax audits at KPP Pratama Padang Sidempuan continues to demonstrate a high level of integrity, as reflected in adherence to procedures, transparency, effective communication, and adequate supporting facilities and infrastructure.